Beispiel Nr: 05
$ \text{Gegeben:}\\\text{Hypotenuse} \qquad c \qquad [m] \\ \text{Kathete}\qquad b \qquad [m] \\ \\ \text{Gesucht:} \\ \text{Kathete} \qquad a \qquad [m] \\ \\ a =\sqrt{c^{2} - b^{2} }\\ \textbf{Gegeben:} \\ c=25m \qquad b=24m \qquad \\ \\ \textbf{Rechnung:} \\ a =\sqrt{c^{2} - b^{2} } \\ c=25m\\ b=24m\\ a =\sqrt{(25m)^{2} - (24m)^{2} }\\\\a=7m \\ \small \begin{array}{|l|} \hline c=\\ \hline 25 m \\ \hline 250 dm \\ \hline 2,5\cdot 10^{3} cm \\ \hline 2,5\cdot 10^{4} mm \\ \hline 2,5\cdot 10^{7} \mu m \\ \hline 0,025 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 24 m \\ \hline 240 dm \\ \hline 2,4\cdot 10^{3} cm \\ \hline 2,4\cdot 10^{4} mm \\ \hline 2,4\cdot 10^{7} \mu m \\ \hline 0,024 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline 0,007 km \\ \hline \end{array}\\$